2013
DOI: 10.1175/jcli-d-12-00696.1
|View full text |Cite
|
Sign up to set email alerts
|

A Decomposition of Feedback Contributions to Polar Warming Amplification

Abstract: Polar surface temperatures are expected to warm 2–3 times faster than the global-mean surface temperature: a phenomenon referred to as polar warming amplification. Therefore, understanding the individual process contributions to the polar warming is critical to understanding global climate sensitivity. The Coupled Feedback Response Analysis Method (CFRAM) is applied to decompose the annual- and zonal-mean vertical temperature response within a transient 1% yr−1 CO2 increase simulation of the NCAR Community Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
178
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 241 publications
(196 citation statements)
references
References 48 publications
4
178
0
1
Order By: Relevance
“…An annual mean cloud cooling effect at the top of the atmosphere may be a consequence of negative shortwave feedbacks in summer offsetting year-round positive longwave feedbacks, and clouds in the Arctic not increasing in height as much as clouds in other places, reducing top-of-atmosphere longwave cloud effects (30). Such annual mean top-of-atmosphere analysis, however, obscures the important role of clouds in altering the winter surface temperature and lapse rate of the lower troposphere (31), and in suppressing Arctic air formation. A year-round increase in cloud fraction damps the seasonal cycle of surface temperature, via increased shortwave reflection during summer and stronger longwave heating during winter, and is therefore in line with proxy evidence of equable climates.…”
Section: Discussionmentioning
confidence: 99%
“…An annual mean cloud cooling effect at the top of the atmosphere may be a consequence of negative shortwave feedbacks in summer offsetting year-round positive longwave feedbacks, and clouds in the Arctic not increasing in height as much as clouds in other places, reducing top-of-atmosphere longwave cloud effects (30). Such annual mean top-of-atmosphere analysis, however, obscures the important role of clouds in altering the winter surface temperature and lapse rate of the lower troposphere (31), and in suppressing Arctic air formation. A year-round increase in cloud fraction damps the seasonal cycle of surface temperature, via increased shortwave reflection during summer and stronger longwave heating during winter, and is therefore in line with proxy evidence of equable climates.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have stressed the close connections between these processes. The surface albedo feedback (SAF) mechanism is reputed to have been an important contributor to the loss of Arctic sea ice over the last few decades (Screen and Simmonds, 2010b;Crook et al, 2011;Taylor et al, 2013). By synthesizing a variety of remote sensing and field measurements, both Flanner et al (2011) and Hudson (2011) concluded that the change in the radiative impact of the Arctic sea ice at the top of the atmosphere in the period 1979-2008 has been a reduced cooling of about 0.1 Wm −2 .…”
Section: Feedback Mechanismsmentioning
confidence: 99%
“…According to the example above, the cloud feedback plays the leading role if the sea ice-albedo feedback is disabled. If the sea ice-albedo feedback is active, it can dominate (Taylor et al, 2013). Winton (2006) found that the Arctic amplification arises from "a balance of significant differences in all forcings and feed-backs between the Arctic and the globe".…”
Section: Arctic Amplificationmentioning
confidence: 99%